The life and work of Yvonne Bryceland : an arts-based investigation - Hofer, Alison Renee (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT: This dissertation spotlights South African actress and theatre practitioner Yvonne Bryceland, who earned respect and admiration during her lifetime but has largely been marginalised in South African theatre history. Chapter One addresses the motivations and methods for the study, offering an explanation of my context as an artistic researcher/educator. A brief biography of Bryceland is provided followed by a description of the extensive process of gathering information from a variety of sources, including personal communications and interviews with friends, colleagues and family members, as well as archival material and documented footage of staged and filmed performances. The various approaches taken in discussing Bryceland’s quality of acting are explained, and reasons for how and why new discoveries and adaptations were made during the research process. In Chapter Two, Bryceland’s life story is captured and distilled in an arts-based research artefact, Dancing with Darkness. The screenplay as heuristic was used to reveal Bryceland as the central character in a dramatic period of South African theatre history. From this focal point, further discussion about Bryceland is offered exploring three distinct, but overlapping, aspects, namely: the extraordinary quality of her acting work; her collaborations with well-known playwright Athol Fugard; and her establishment, with Fugard and her husband Brian Astbury, of The Space as a radically alternative theatre. Chapter Three discusses how the quality of Bryceland’s acting work often led colleagues and audiences to describe her performances in words that capture a sense of magic and awe. In attempting to describe Bryceland’s acting techniques and position her as an exemplary South African actress, this chapter reveals how the discussion was broadened and deepened to incorporate metaphysical notions for which the Spanish concept of duende was applied and adapted as a potent symbol for Bryceland’s artistry. Together with Fugard, Bryceland contributed some outstanding plays to South Africa theatre history, which offer traces of the country’s social and political evolution from the 1970s to 1990s. Chapter Three explores the intensity of the artistic symbiosis between Bryceland and Fugard, and their focus on their theatre art as a means to express truth. Chapter Four describes what led to the establishment of The Space theatre by Bryceland, Fugard and Astbury; to what extent the theatre work being done at The Space was different; and Bryceland’s determination that the theatre remain open to casts and audiences of all races. This chapter in particular reveals The Space as a veritable hothouse for new talent, providing well-known actors, writers and directors their first opportunities in theatre practice, as well as serving as a catalyst for the establishment of similar theatres in South Africa. The concluding chapter highlights the significant impact that Bryceland has had on the nature and voice of South African theatre, by her contributions to the philosophy and practice of diverse practitioners, and as such positions Bryceland as deserving consideration as one of the key figures in South African theatre history.